GEOCHEMICAL EVALUATION FOR HEAVY METALS IN STREAM SEDIMENTS OF KANO RIVER DRAINAGE BASIN, NORTH WESTERN NIGERIA - Garba, I.; Tende, W. A.; Schoeneich, K.; Tahir, A.G; Danbatta U. A, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2017)
Geochemical investigation was carried out to ascertain the levels of heavy metal pollution in rivers around Kano River. Stream sediments were collected from upstream to downstream and geochemical analysis for six heavy metal elements (Cr, Co, Ni, Cu, Pb, and Mn). Heavy metal concentration in stream sediments was determined using XRF. Three pollution criteria (Contamination factor, enrichment factor and index of Geo accumulation) were used to assess the level of pollution in these sediments. Computed results revealed low contamination to considerable contamination when contamination factor was used. Most samples displayed low contamination. Application of enrichment factor reveals samples were deficient to enrichment to moderate enrichment. Index of geo accumulation reveals all samples had uncontaminated characteristics. From geochemical point of view, pollution levels within the study area were generally low but caution should be taken in areas like Wailari where significant pollution was observed.